Developing and validating a vocational classroom-based assessment questionnaire for the vocational food and nutrition teachers - Combrinck, Celeste (University of Pretoria, 2025)
Thesis (PhD (Assessment and Quality Assurance in Education and Training))--University of Pretoria, 2024.